2019
DOI: 10.1523/jneurosci.3068-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous tagging reveals differential regulation of Ca2+ channels at single AZs during presynaptic homeostatic potentiation and depression

Abstract: Neurons communicate through Ca2+-dependent neurotransmitter release at presynaptic active zones (AZs). Neurotransmitter release properties play a key role in defining information flow in circuits and are tuned during multiple forms of plasticity. Despite their central role in determining neurotransmitter release properties, little is known about how Ca2+ channel levels are modulated to calibrate synaptic function. We used CRISPR to tag the Drosophila CaV2 Ca2+ channel Cacophony (Cac) and, in males in which all… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 81 publications
(144 reference statements)
4
93
1
Order By: Relevance
“…New work has reported that endogenous synaptic protein levels of the active zone protein Bruchpilot (Brp, an ELKS/CAST homolog, (Kittel et al, 2006)) and Ca V 2/Cacophony do not change upon PHD induction (Gratz et al, 2019). These data are consistent with a model in which the deceased release associated with PHD is executed-at least in part-through functional modulations of existing active zone components.…”
Section: Phd Versus Phpsupporting
confidence: 63%
See 4 more Smart Citations
“…New work has reported that endogenous synaptic protein levels of the active zone protein Bruchpilot (Brp, an ELKS/CAST homolog, (Kittel et al, 2006)) and Ca V 2/Cacophony do not change upon PHD induction (Gratz et al, 2019). These data are consistent with a model in which the deceased release associated with PHD is executed-at least in part-through functional modulations of existing active zone components.…”
Section: Phd Versus Phpsupporting
confidence: 63%
“…Several labs confirmed increased Brp abundance during rapid or sustained PHP expression Goel, Li, & Dickman, 2017;Gratz et al, 2019). Intriguingly, acute and prolonged glutamate receptor perturbation also increases the fluorescence intensity of fluorescently-tagged presynaptic voltage-gated Ca 2+ channels ( Figure 4; Gratz et al, 2019;Li, Goel, Wondolowski, et al, 2018). Moreover, the fluorescence intensity of antibody stainings of several other presynaptic proteins-RBP, Unc13A, and Syntaxin-1A (Syx-1A)-increased after acute glutamate receptor inhibition .…”
Section: Active Zone Structurementioning
confidence: 88%
See 3 more Smart Citations